Literature Review: Sedentary Behavior In Outdoor Education Learning Elementary School Students - Hernawan (Gladi : Jurnal Ilmu Keolahragaan, 2023)
Sedentary behavior is a wakeful behavior or activity characterized by expenditure of energy such as sitting or lying down, as distinct from passive behavior. Sedentary behavior in outdoor education learning is a learning strategy that is carried out outdoors. Learning strategies like this are carried out by inviting students to unite with nature and do some outdoor activities. The purpose of this study was to determine the factors of sedentary behavior in outdoor education learning. Method: This study uses a literature study approach. Article search used 2 databases, namely Google Scholar and Pubmed with the keywords outdoor education and sedentary behavior. The criteria for the article are original published from 2013 to 2023. Results: Of the 16 articles that have been reviewed, the results show that all articles explain sedentary habits as bad habits that are prone to disease. There fore outdoor learning is one of the factors to reduce the occurrence of diseases that come as a result of sedentary habits, because a child will be more active and move a lot when outside the room. Conclusion: The results of the review of the 16 articles explained that there are factors that influence sedentary behavior in a child which can make a child lazy to move and do other activities. There fore outdoor learning is one of the supporting factors for reducing the occurrence of diseases that come as a result of sedentary habits, because a child will be more active and move a lot when outside the room